The Contributing Factors of the Regional Income Disparity in China - Li, Xin (Université d'Ottawa | University of Ottawa, 2005)
Based on the neo-classical growth theory, this paper intends to use panel data approach to find out the contributing factors of the regional disparity in China since the economic reform in 1978. After comparing effects of several main factors: non-agricul